2019
DOI: 10.1186/s12905-019-0829-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of female sexual dysfunction in allied health workers: a cross-sectional pilot study in a tertiary hospital in Singapore

Abstract: BackgroundFemale sexual dysfunction (FSD) is increasingly being identified as a problem around the world. Women can have problems in various parts of the sexual cycle - desire, arousal, lubrication, orgasm or they may experience pain related to sexual activity. The only study involving Singapore with regard to sexual dysfunction in women, the Asian Global Studies of Sexual Attitudes and Behaviours in 2002, reported that Singapore had one of the lowest age-standardised sexual dysfunction rates of 32% compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…It was reported that sexual function screening scores were similar in the nurse and doctor groups and higher than the hospital administrative staff group 22 . In another study conducted in Singapore, nurses were found to have a lower FSD prevalence rate than their other allied health counterparts (Rehabilitation, Nutrition and Dietetics, Medical Social Services and Pharmacy) 23 .…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that sexual function screening scores were similar in the nurse and doctor groups and higher than the hospital administrative staff group 22 . In another study conducted in Singapore, nurses were found to have a lower FSD prevalence rate than their other allied health counterparts (Rehabilitation, Nutrition and Dietetics, Medical Social Services and Pharmacy) 23 .…”
Section: Discussionmentioning
confidence: 91%
“…It is evident from many studies that some factors had unclear effects on FSD, such as race, education, employment, parity, being in a relationship, frequency of sexual intercourse, smoking, and alcohol consumption [ 38 ]. Thereby a study from Singapore, hospital nurses were less likely to develop FSD [ 39 ], and employed women were considerably more likely to present with vaginismus than unemployed women [ 40 ]. In Malaysia and Iran, women who received education up to secondary school and homemakers were more at risk of FSD [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any change in sexual drive may indicate a sexual disorder. Based on data in Singapore, 56% of women expe-rience sexual disorders (Safdar et al, 2019). Changes in sexual drive can affect the household and psychological well-being of partners.…”
Section: Introductionmentioning
confidence: 99%